PENGARUH LOKASI, KELENGKAPAN PRODUK, KUALITAS PRODUK, PELAYANAN, HARGA, DAN KENYAMANAN BERBELANJA TERHADAP MINAT BELI ULANG KONSUMEN PADA LOTTE MART BEKASI JUNCTION - Rosita, Rahmi (E-Journal Widya Ekonomika, 2018)
Indonesia with a population of about 240 million more a potential market for modern retail business. Consumers have many alternatives in choosing where to shop. Therefore the modern market (retail) must consider a variety of factors that will influence the consumer's perception of consumer behavior in choosing the best shopping by consumers.The purpose of this experiment is (1). To test the effect of the location, range of products, product quality, service, price, convenience shopping. (2). This study also aims to determine the contribution of these factors is most dominant in influencing consumer buying interest re. The study involved 100 respondents taken by purposive sampling with questionnaires instrument. Measurements with Likert scale. The analysis technique processed using SPSS. This research is a quantitative and qualitative research, using multiple linear regression. The results showed that: (1). There is a significant relationship between the variables of location, range of products, product quality, service and shopping convenience to the buying interest re-consumers, except for the variable service negatively affect the buying interest re-consumers. (2) It was found that the price variable has the most dominant influence on all six variables decider against the consumer purchase interest.